Numerical Investigation of Wind Erosion to the Grooved Concrete Wall Surface under a Wind-Blown Sand Movement - Shanqun Chen; Runchao Tang; Longzhu Zhang; Bin Liao (Advances in Materials Science and Engineering)
Wind erosion to the grooved concrete wall surface under a wind-blown sand movement was numerically studied. Particularly, the influencing factors that affect the wind erosion to the grooved concrete wall surface were systematically investigated by using the RNG k−ε turbulence model combined with the discrete phase model (DPM). It was found that, under a relatively low impact angle, the damage mechanism to the grooved wall surface is wind-blown sand impact, and the erosion rates of the grooved wall surfaces are higher than those of the smooth wall surfaces. By contrast, under a relatively high impact angle, the damage mechanism to the grooved wall surface transfers to the microcutting effect, and the erosion rates show an opposite trend. The optimization rates between the erosion of grooved and smooth wall surfaces increase with increasing groove size or groove number. However, the damage mechanism to the grooved wall surface is hardly changed by expanding the groove area. The erosion rate distribution and the optimization rates of the groove wall surfaces are not significantly changed by adjusting the spacing between the grooves alone. When the groove shape changes from semicircular to rectangular, the erosion rate distribution is significantly changed, and the wear resistance of the changed grooved wall surface gets better.